Legal Considerations in the Disparity of the Judge's Decisions Have Fulfilled a Sense of Justice - Nur Risqy Afieany Rahim (Universitas Negeri Gorontalo, 2023)
The purpose of this research is to know and analyze aboutthe cause of the disparity in judge decisions that occurred in narcotics abuse cases with case number 94/Pid.Sus/2018/PN.Gto and number 138/Pid.Sus/2019/PN.Gto and to find out and analyze whether the sentence imposed by the judge In this disparity case, it is in accordance with justice or not with normative research methods using a case approach. The technique used is a systematic technique through literature study and using descriptive analysis techniques as a support.The results of the analysis in the resulting research are first in the disparity case number 94/Pid.Sus/2018/PN.Gto and number 138/Pid.Sus/2019/PN. Gto there are factors that influence the judge's decision including legal factors, factors evidence, and individual historical factors or trial facts. The two criminal sentences carried out by the judge, in this case, are considered to be far from justice because the results of the judge's decision are far greater in the second case than the first due to several influencing factors